1979
DOI: 10.1111/j.1365-2761.1979.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatomas in Atlantic tomcod Microgadus tomcod (Walbaum) collected in the Hudson River estuary in New York

Abstract: Incidental observations of Atlantic tomcod during routine laboratory processing revealed that a portion of the adult population, collected during the 1977-78 spawning season had enlarged livers containing dark coloured tumours and other abnormalities. Ofthe total of 264 livers collected between 16 January and 27 February 1978 and grossly examined for prevalence of abnormalities, 25% appeared to contain neoplastic nodules and hepatocellular carcinoma. One liver contained a massive tumour (7 x 12 mm) that involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…In natural waters, it is difficult to isolate substances which alone are capable of inducing neoplasia formation. For the epizootics of hepatic neoplasias in the Baltic Sea (Falkmer et al 1977), Duwamish River (Washington, USA) (Pierce et al 1978), and the Hudson River estuary (New York, USA) (Smith et al 1979), PCBs (polychlorinated biphenyls) were the substances initially blamed for causing the disease. What seemed to be particularly strong evidence was provided by the case of the myxine hepatomas.…”
Section: Z Wmentioning
confidence: 99%
“…In natural waters, it is difficult to isolate substances which alone are capable of inducing neoplasia formation. For the epizootics of hepatic neoplasias in the Baltic Sea (Falkmer et al 1977), Duwamish River (Washington, USA) (Pierce et al 1978), and the Hudson River estuary (New York, USA) (Smith et al 1979), PCBs (polychlorinated biphenyls) were the substances initially blamed for causing the disease. What seemed to be particularly strong evidence was provided by the case of the myxine hepatomas.…”
Section: Z Wmentioning
confidence: 99%
“…PAH have been implicated in the etiology of papillomas and epidermal carcinomas in bottom-dwelling freshwater brown bullheads Ictalurus nebulosus (Harshbarger 1981, Baumann et al 1982, Black 1983b, Baumann & Harshbarger 1985 and white suckers Catostomus con]-mersoni (Sonstegard 1977). PAH have also been implicated as the etiological agent of hepatic neoplasia in fish from highly polluted sites (Smith et al 1979. Malins et al 1987.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns are identical to those well known to occur in the liver neoplasms impaired by considerable anthropogenic input of various hepatotoxin, carcinogenic and/or carcinogenic promoters. [9][10][11][12][13][14][15][16] The time-course observation of the uptake and elimination of BHT showed that BHT was rapidly absorbed into the fish body through the digestive tract, distributed to various tissues by blood, taken to the liver, and then carried away to the alimentary tract with bile. The uptake pathway of BHT in Japanese eel was similar to those of nonylphenol ethoxylated, sodium linear alkylbenzene sulfonate and sodium alkylsulfate in fish.…”
Section: Resultsmentioning
confidence: 99%